The Role of Tax Amnesty in Increasing Tax Revenue and State Income in Indonesia - Setiyana, Putri; Rif'an, Aenur; Bayu, Oktaviana; Susanto, Ryan (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2025)
This article discusses the effectiveness of the tax amnesty policy in increasing state revenue and taxpayer compliance in Indonesia. Using a qualitative approach based on literature review, this study examines the implementation mechanisms of the 2016–2017 tax amnesty program and its impact on the national taxation structure. The analysis shows that the program successfully collected Rp135 trillion in redemption payments from 965,983 taxpayers and resulted in asset declarations amounting to Rp4,855 trillion—equivalent to 40% of the national GDP. However, the realization of asset repatriation only reached 14.7% of the target, indicating challenges in returning offshore assets. This program contributed to strengthening the tax database and promoting voluntary compliance, although it still faces challenges such as perceptions of injustice and low tax literacy. The article proposes three follow-up strategies: consistent law enforcement after the amnesty period, optimization of the taxpayer database through inter-agency and technological integration, and enhanced tax education. In conclusion, tax amnesty has the potential to be an effective fiscal instrument if accompanied by structural reforms and well-measured long-term strategies.